Comparative Structural and Economic Analysis of Rainbow Trout (Oncorhynchus mykiss) Hatcheries with Different Production Capacities in Kahramanmaraş Province, Turkey - Güneş, Yılmaz Ebru; Koprucu, Kenan (My University, 2019)
In this study, the structural and economic aspects of rainbow trout (Oncorhynchus mykiss) hatcheries with thedifferent production capacities in Kahramanmaraş Province of Turkey were compared. The commercial structure of thisenterprises was 60% person-family and 40% company-partnership. Statistically, the medium-sized (96.88%) hatcherieshave higher capacity usage rate than the the small (69.98%) and large-sized (60.0%) hatcheries (P?0.01). However, theproduction efficiency of the small (64.50%) and medium-sized (63.99%) enterprises were higher (P?0.01) than thelarge-sized enterprises. Average active capital was US $181 165 in the small-sized, $436 147 in the medium-sized and$1 271 634 in the large-sized enterprises. Gross and net income values were $40 213 and $4 215 in the small-sizedenterprises, $189 412 and $74 268 in the medium-sized enterprises and $901 961 and $69 074 in the large-sizedenterprises. The medium-sized enterprises have highest economic rantability (17.03%) followed by the large (5.43%)and small-sized (2.33%) enterprises (P?0.01). Differences in the structural characteristics of existing enterprises directlyaffect their capacity usage rate and production efficiency.
Keywords: Biyoloji; Nüfus İstatistikleri Bilimi; Balıkçılık